Improving Children's Social Emotional Development Through “Uno Stacko” Games - Nauratuddini; Tursina, Ade; Balqis Mutia, Nur (Seulanga : Jurnal Pendidikan Anak, 2024)
This study aims to determine the improvement of children's social emotional development through uno stacko games at TAUD Luqmanul Hakim Kindergarten, Langsa City. The research method used is class action research (PTK). The research subjects in this study were children aged 5-6 years, totalling 8 people consisting of 4 girls and 4 boys. Indicators of social emotional development aspects assessed include: familiarity playing with peers; having empathy and sympathy; sharing with others; respecting the rights / opinions / work of others; using socially acceptable ways of solving problems; being cooperative; being tolerant; expressing emotions in accordance with existing conditions; recognise manners and courtesy in accordance with local socio-cultural values. Data collection was conducted using observation, interview, and documentation methods. The results showed that there was an increase in children's social emotional development in cycle I with a value of 61.75% to 92.25% in cycle II. So it can be concluded that the uno stacko game can improve children's social emotional development at TAUD Luqmanul Hakim Kindergarten, Langsa City.